Cardiovascular and respiratory status in mechanically ventilated asphyxiated term infants: comparison between hypothermic and control group - Lista, G.; Pogliani, L.; Fontana, et al., P. (Acta Biomedica Atenei Parmensis, 2004)
Objective: To evaluate cardiorespiratory changes in hypothermic asphyxiated ventilated infants compared with controls. Study Design: Retrospective chart analysis with historical controls. Cardiorespiratory status of 10 asphyxiated newborns in hypothermia (H) (32°-34°C) (H group) was compared with that one of 11 asphyxiated newborns [control group, (C group)]. Results: 3/10 patients in H group needed an increased mean tidal volume (from 5.8 to 8 ml/Kg) during hypothermia when temperature reached a value of 32°C, to maintain adequate gas exchange. Length of mechanical ventilation was similar in the two groups (H=5.4±4.4 vs C=2.8±2.7 days, p=ns). Heart rate, similar at the baseline (H group: 129±11 beats/min; C group: 129±12 beats/min), dropped to an average of 102±10 beats/min (p<0.05) during cooling in H group, while it remained stable in C group. Mean arterial blood pressure, comparable at birth, increased by a median of 8 mmHg during hypothermia (p=ns). Conclusions: Hypothermia induces mild changes in cardiovascular status and in lung mechanics.